Copper electrode slurry, metal electrode and preparation method thereof, and photovoltaic cell

By using copper electrode slurry and laser processes to prepare copper electrodes for silicon heterojunction solar cells, the problems of cumbersome processes, high cost and insufficient binding force in the prior art are solved, and efficient and low-cost copper electrode preparation is achieved, which improves the Conversion efficiency and stability of solar cells.

CN119480208AInactive Publication Date: 2025-02-18GUANGDONG UNIV OF TECH +1

Patent Information

Application Number
CN202310950155.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems such as cumbersome process, high cost, poor conductivity and insufficient binding force when preparing copper electrodes of silicon heterojunction solar cells, which limits the conversion efficiency and cost-effectiveness of solar cells.

Method used

Using a copper electrode slurry, including a metal composition, a dispersion reducing agent and a composite curing agent, metal electrodes are prepared by laser process, simplifying the process flow, and improving the aspect ratio and binding force of the copper electrode.

Benefits of technology

The production cost of solar cell energy electrodes is reduced, the conductivity of copper electrodes and the bonding force with the substrate is improved, the durability and stability of solar cells are enhanced, and the light conversion efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480208A_ABST
    Figure CN119480208A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic cells, and provides copper electrode slurry, a metal electrode, a preparation method of the metal electrode and a photovoltaic cell. The copper electrode slurry comprises a metal composition, a dispersion reducing agent, a composite curing agent and an optional solvent, the metal composition at least comprises copper powder and optional gold powder and / or silver powder; the composite curing agent comprises thermosetting resin and a latent curing agent; wherein the mass ratio of the metal composition to the composite curing agent is (7-30): 1. The copper electrode paste provided by the invention replaces expensive silver paste, so that the manufacturing cost of a solar cell energy electrode is greatly reduced. According to the method for preparing the metal electrode, the position of the copper electrode can be precisely machined, damage to the amorphous silicon layer is avoided, remelting and solidification of the copper electrode are achieved through multiple times of laser scanning, and the problem that the adhesive force between the copper electrode and the substrate is poor is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic cells, and in particular to a copper electrode slurry, a metal electrode and a preparation method thereof, and a photovoltaic cell. Background Art

[0002] Silicon heterojunction (HJT) cells are a type of high-efficiency solar cell. They have become one of the most promising solar cell technologies due to their advantages such as simple process, high conversion efficiency, low-temperature process, and double-sided power generation. The metal grid electrode is the most important structure and material in silicon heterojunction cells. Its main function is to collect carriers generated by the photovoltaic effect, thereby drawing out the current generated by the photovoltaic effect.

[0003] At present, the most commonly used method for preparing electrodes in the industry is screen printing silver paste, which has the advantages of simple and mature process and suitable for mass production. However, due to the precision of the printing plate, the electrode aspect ratio is small, the shading area is large, the screen printing process is becoming more and more difficult, and the yield rate caused by virtual printing and broken grids has dropped significantly, which limits the further improvement of the conversion efficiency of solar cells. On the other hand, due to the inherent characteristics of HJT cells, the processing technology needs to be controlled at around 200°C, and low-temperature silver paste needs to be used. However, low-temperature silver paste has poor conductivity, high contact resistance with ITO film (Transparent Conductive Oxide), poor printing performance, and a large weight gain of the paste of the heterojunction battery, accounting for about 30-40% of the cost of the entire heterojunction processing battery. In addition, the price of silver paste is expensive, which makes the manufacturing cost of solar cells high, which is not conducive to the development of batteries in the direction of high efficiency and low cost.

[0004] In order to reduce costs and increase efficiency, more and more solar cell manufacturers have turned to the development of copper electrodes with high conductivity and low cost. The most commonly used method at present is electroplating. The preparation of copper grid electrode by electroplating is to first deposit a layer of seed copper on the surface of ITO, then pattern the mask, and then electroplate copper and tin. However, this method needs to consider the subsequent etching and removal of the mask and seed layer. The process is relatively cumbersome, and the bonding strength between the copper electrode and the substrate has always been a problem in the industry. In addition, since there is no mature electroplating equipment developed specifically for heterojunction batteries on the market, the equipment is basically transformed from the traditional PCB (printed circuit board) industry, so the operating cost and processing quality cannot fully meet the expected requirements, which runs counter to the goal of reducing costs and increasing efficiency.

[0005] Therefore, it is of great significance to develop a method for preparing copper electrodes for silicon heterojunction solar cells with simple process and low cost. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and to provide a copper electrode slurry, a metal electrode prepared from the copper electrode slurry, a method for preparing a metal electrode, and a photovoltaic cell. The copper electrode slurry provided by the present invention replaces the use of expensive silver paste, greatly reducing the production cost of solar cell electrodes; and the copper electrode slurry has good dispersibility and high reduction rate, and the addition of a composite curing agent effectively improves the bonding force between the inside of the copper circuit and the substrate, increasing the durability and stability of the solar cell.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a copper electrode slurry, comprising a metal composition, a dispersing reducing agent, a composite curing agent and optionally a solvent; the metal composition comprises at least copper powder, and optionally gold powder and / or silver powder; the composite curing agent comprises a thermosetting resin and a latent curing agent; wherein the mass ratio of the metal composition to the composite curing agent is (7-30):1.

[0008] The second aspect of the present invention provides a metal electrode, which is prepared using the copper electrode slurry described in the first aspect of the present invention.

[0009] The third aspect of the present invention provides a method for preparing a metal electrode, which uses the copper electrode slurry and laser process described in the first aspect of the present invention to prepare the metal electrode.

[0010] A fourth aspect of the present invention provides a photovoltaic cell, comprising a metal electrode, wherein the metal electrode is prepared using the copper electrode slurry described in the first aspect of the present invention, or the metal electrode is prepared using the method described in the second aspect of the present invention.

[0011] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0012] (1) The copper electrode slurry provided by the present invention uses a metal composition containing copper powder as a precursor material to prepare a coating to prepare a copper electrode, replacing the use of expensive silver paste, greatly reducing the production cost of solar cell electrodes, and can well meet the needs of high efficiency and low cost in industrial production.

[0013] (2) The method for preparing metal electrodes provided by the present invention can accurately process the position of the copper electrode due to the high controllability of laser processing, thus solving the current problem of screen printing accuracy and avoiding damage to the amorphous silicon layer. The prepared copper electrode has a large aspect ratio, which can effectively improve the light conversion efficiency.

[0014] (3) The method for preparing a metal electrode provided by the present invention realizes the remelting and solidification of the copper electrode through multiple laser scanning, which effectively solves the problem of poor adhesion between the copper electrode and the substrate, while avoiding the high-temperature curing step of the sintering furnace and reducing damage to the amorphous silicon layer.

[0015] (4) The method for preparing metal electrodes provided by the present invention avoids a series of complex processes such as masking, exposure, development, and etching, thereby simplifying the process and reducing costs. Moreover, the processed pattern can be directly and flexibly changed through drawing software such as CAD, so that complex copper electrode circuit morphologies can be processed more flexibly.

[0016] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Shown is a schematic structural diagram of a heterojunction battery in one example.

[0018] Figure 2 The figure shows a process flow chart for preparing copper electrodes for heterojunction batteries in one example.

[0019] Figure 3 The figure shows a schematic diagram of the process for preparing a copper electrode for a heterojunction battery in one example.

[0020] Figure 4 The figure shows a schematic structural diagram of a laser processing system in one example.

[0021] Figure 5 FIG. 1 is a schematic diagram of a laser processing operation in one example.

[0022] Figure 6 Shown is a three-dimensional morphology of a copper electrode of a heterojunction battery in one example.

[0023] Figure numerals: 1-metal electrode; 2-transparent conductive film; 3-p-type amorphous silicon film; 4-n-type amorphous silicon film; 5-intrinsic amorphous silicon film; 6-copper electrode slurry coating; 7-laser; 8-heterojunction battery substrate; 9-laser; 10-attenuation plate; 11-aperture; 12-wave plate; 13-beam expander; 14-reflector; 15-CCD image sensor; 16-galvanometer; 17-field mirror; 18-moving platform. DETAILED DESCRIPTION

[0024] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0025] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0026] The first aspect of the present invention provides a copper electrode slurry, comprising a metal composition, a dispersing reducing agent and a composite curing agent; the metal composition comprises at least copper powder, and optionally gold powder and / or silver powder; the composite curing agent comprises a thermosetting resin and a latent curing agent; wherein the mass ratio of the metal composition to the composite curing agent is (7-30):1.

[0027] It should be noted that, in addition to copper powder, the metal composition may also contain gold powder and / or silver powder, as well as other metal powders with good electrical conductivity. The metal composition may be a combination of one or more of various forms of the above-mentioned metal elements, such as simple substances, oxides, hydroxides or salts, which is not limited and can be selected according to actual needs. For example, the metal composition may be a combination of three metal simple substances of copper, gold and silver, or may be a combination of three metal oxides.

[0028] In one example, the metal composition is in powder form, and the particle size is nanometer scale.

[0029] The copper electrode slurry of the present invention has the advantages of good dispersibility and high reduction rate, and the composite curing agent prepared by using a thermosetting resin and a latent curing agent can make the bonding force of the electrode prepared by the copper electrode slurry higher.

[0030] In one example, the metal composition includes nano copper oxide and / or nano cuprous oxide.

[0031] In one example, the metal composition is solely nano-copper oxide, or solely nano-cuprous oxide.

[0032] In one example, the metal composition is a composition of nano-copper oxide and nano-cuprous oxide. The ratio of the two is not limited and can be adjusted according to the actual sequence. Exemplarily, the mass ratio of nano-copper oxide to nano-cuprous oxide can be (1-5):1.

[0033] In one example, the mass ratio of the metal composition to the composite curing agent is (7-30):1, for example, it can be 7:1, 10:1, 12:1, 15:1, 16.4:1, 18:1, 20:1, 25:1, 28:1, or 30:1.

[0034] In a preferred embodiment, the mass ratio of the metal composition to the composite curing agent is (15-20):1.

[0035] In order to further improve the performance of the copper electrode slurry and prepare a metal electrode with better physical properties, one or more of the characteristics may be optimized.

[0036] In one example, the thermosetting resin is at least one selected from epoxy resin, polyurethane-modified epoxy resin, acrylic-modified epoxy resin, polyamide resin, polyurethane resin and acrylic resin.

[0037] In one example, the thermosetting resin is an epoxy resin.

[0038] In one example, the latent curing agent includes a latent amine curing agent and / or an imidazole curing agent. The latent curing agent can be a latent amine curing agent alone, an imidazole curing agent, or a combination of a latent amine curing agent and an imidazole curing agent.

[0039] Exemplarily, the latent amine curing agent includes MY-24, MY-25 and MY-HK-1. Exemplarily, the imidazole curing agent includes PN-23J, PN-50, PN-23, PN-31 and PN-40.

[0040] In one example, the latent curing agent is a latent amine curing agent and an imidazole curing agent. The mass ratio of the latent amine curing agent and the imidazole curing agent is not limited and can be freely adjusted according to actual needs.

[0041] Exemplarily, the mass ratio of the thermosetting resin to the latent curing agent may be (4-6):1, for example, 4:1, 5:1, or 6:1.

[0042] The combination of latent amine curing agent and imidazole curing agent, and thermosetting resin, especially epoxy resin therein, to form a composite curing agent can make the copper electrode slurry cure faster and improve the bonding strength between the copper electrode slurry and the contact surface.

[0043] In one embodiment, the reducing dispersant is selected from at least one of polyvinyl pyrrolidone and its derivatives. The specific type of the derivative is not limited, for example, it can be a copolymer of polyvinyl pyrrolidone, or a reactant of polyvinyl pyrrolidone and other compounds, as long as the derivative can play a similar or better dispersing and reducing role as polyvinyl pyrrolidone.

[0044] In one example, the mass ratio of the metal composition to the dispersing reducing agent is (2-9):1, for example, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 8.74:1, 9:1.

[0045] In a preferred embodiment, the mass ratio of the metal composition to the dispersing reducing agent is (2.5-6):1.

[0046] The present invention selects polyvinyl pyrrolidone and its derivatives which have both dispersing and reducing effects as dispersing reducing agents, and limits the mass ratio of the metal composition and polyvinyl pyrrolidone and its derivatives, so that the copper electrode slurry has the advantages of good dispersibility and high reduction rate, improves the process efficiency of subsequent copper electrode preparation, and makes it easier to obtain copper electrodes with uniform thickness.

[0047] The type of solvent is not specifically limited, as long as it can dissolve the metal composition, disperse the reducing agent, and the composite curing agent, and does not react with the solute components. In one example, the solvent can be selected from C1-C6 low-carbon alcohols, or other types of organic solvents can be selected in the art.

[0048] In one example, the low-carbon alcohol includes at least one of ethylene glycol, polyethylene glycol, pentanol, propanol, butanol and isobutanol.

[0049] In one example, the mass ratio of the metal composition to the solvent is (0.3-2):1, for example, 0.3:1, 0.34:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.86:1, or 2:1.

[0050] In a preferred embodiment, the mass ratio of the metal composition to the solvent is (1-1.6):1.

[0051] In one example, the mass ratio of the solvent to the dispersing reducing agent is (1.8-14):1, for example, it can be 1.8:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 13.6:1, 14:1.

[0052] In a preferred embodiment, the mass ratio of the solvent to the dispersing reducing agent is (2-5):1.

[0053] By limiting and optimizing the mass ratio of the metal composition and the solvent, as well as the mass ratio of the dispersing reducing agent and the solvent, the solid content of the copper electrode slurry can be controlled within an appropriate range, so that the copper electrode slurry contains more metal composition while having good dispersibility, which facilitates the coating of the copper electrode slurry and improves the thickness and uniformity of the prepared metal electrode.

[0054] In one example, the copper electrode slurry includes nano copper oxide, polyvinyl pyrrolidone, epoxy resin, latent amine curing agent, imidazole curing agent and ethylene glycol, wherein the proportion of each component is within the above-listed proportion range.

[0055] The present invention also provides a method for preparing a copper electrode slurry, which comprises the following steps:

[0056] (i) mixing the reducing dispersant and the solvent in the formulated amount in batches for multiple times to obtain a mixed solution under the combined action of heating, magnetic stirring and ultrasonic vibration;

[0057] (ii) adding the metal composition and the composite curing agent in the formulated amount to the mixed solution obtained in step (1) in batches for multiple times, and obtaining a copper electrode slurry under the combined action of heating, magnetic stirring and ultrasonic vibration.

[0058] The heating in steps (i) and (ii) can be performed in a water bath at 45-65° C. The number of batches is not limited and can be adjusted freely according to the different formulation contents.

[0059] The process conditions for heating, magnetic stirring and ultrasonic vibration in steps (i) and (ii) are not particularly limited and can be freely adjusted according to the amount and mixing state of the solution.

[0060] The second aspect of the present invention provides a metal electrode, which is prepared using the copper electrode slurry described in the first aspect of the present invention.

[0061] In one example, the metal electrode is a metal electrode in a solar cell, a secondary battery, a circuit board, a light emitting diode or a microelectronic device.

[0062] Preferably, the metal electrode is a grid electrode of a solar cell, for example, the metal electrode is a copper grid electrode of a heterojunction cell.

[0063] The third aspect of the present invention provides a method for preparing a metal electrode, which uses the copper electrode slurry and laser process described in the first aspect of the present invention to prepare the metal electrode.

[0064] The method for preparing metal electrodes provided by the present invention can be applied to a variety of fields, such as: solar cells, secondary batteries, circuit boards, light-emitting diodes or microelectronic devices, and can also be batteries or instruments and equipment in other technical fields. As long as they contain metal electrodes prepared by the method of the present invention, they are within the protection scope of the present invention.

[0065] The present invention also provides a method for preparing a solar cell grid line electrode, which adopts the copper electrode slurry and laser process described in the first aspect of the present invention to prepare a metal electrode, and particularly relates to a method for preparing a heterojunction solar cell grid line electrode.

[0066] In one example, the basic structure of a heterojunction cell is referred to Figure 1As shown, it mainly includes an n-type single crystal silicon wafer 4 (c-Si), an intrinsic amorphous silicon thin film layer 5 (ia-Si:H), an amorphous silicon film layer 3 (pa-Si:H), a transparent conductive film 2 (ITO) and a metal gate electrode 1.

[0067] In one embodiment, a method for preparing a heterojunction solar cell comprises the following steps:

[0068] (I) performing texturing and cleaning on an n-type single crystal silicon wafer, i.e. forming a texturing surface ("pyramid structure") on the surface of the silicon wafer;

[0069] (II) deposition of an amorphous silicon film, including deposition of an intrinsic amorphous silicon film and a doped amorphous silicon film, firstly depositing an intrinsic amorphous silicon film (ia-Si:H) and a p-type amorphous silicon film (pa-Si:H) on the front side of an n-type single crystal silicon wafer (c-Si), and then depositing an intrinsic amorphous silicon film (ia-Si:H) and an n-type amorphous silicon film (na-Si:H) on the back side of the silicon wafer to form a back surface field;

[0070] (III) Depositing transparent oxide conductive films on both sides of the cell.

[0071] In one example, in step (I), the texturing and cleaning can cause the incident light to be reflected and refracted multiple times on the surface of the single crystal silicon wafer, thereby extending the optical path, increasing the photogenerated carriers, and avoiding the recombination of carriers at the junction interface caused by defects and impurities introduced by uncleanliness.

[0072] In one example, in step (II), the amorphous silicon film is deposited by plasma enhanced chemical vapor deposition and hot wire chemical vapor deposition. Superior surface passivation ability is an important condition for obtaining higher cell efficiency. By utilizing the excellent passivation effect of amorphous silicon, the minority carrier lifetime of silicon wafers can be greatly improved.

[0073] In one example, in step (III), the deposition method of the transparent conductive film includes various physical vapor deposition (PVD), chemical vapor deposition (CVD), jet pyrolysis and sol-gel. Since amorphous silicon has poor conductivity, adding a transparent conductive film between the electrode and the amorphous silicon layer during the manufacturing process of heterojunction solar cells can effectively increase the collection of carriers, and can also play an anti-reflection role, and is a good window layer material.

[0074] In one example, the intrinsic amorphous silicon film (ia-Si:H) has a thickness of 0.1-10 nm.

[0075] In one example, the thickness of the p-type amorphous silicon film (pa-Si:H) is 0.1-10 nm.

[0076] In one example, the thickness of the n-type amorphous silicon film (na-Si:H) is 0.1-10 nm.

[0077] In one example, the thickness of the transparent conductive film (ITO) is 1-400 nm.

[0078] In one embodiment, the present invention further provides a method for preparing a solar cell grid line electrode, which comprises the following steps:

[0079] (1) placing the copper electrode slurry on the surface of the transparent conductive film of the silicon substrate;

[0080] (2) performing a first laser scan on the copper electrode slurry coating on the surface of the transparent conductive film in step (1);

[0081] (3) performing laser processing N times on the copper electrode slurry of step (2), where N≧2;

[0082] It should be noted that the N-th laser scanning of the copper electrode slurry in step (2) can be specifically interpreted as the N-th laser scanning of the Cu circuit pattern obtained in step (2).

[0083] There is no limitation on the energy of the Nth laser scan, and it can be less than, equal to or greater than the energy of the first laser scan.

[0084] In one example, when the energy of the Nth laser scan is greater than the energy of the first laser scan, the copper electrode can be remelted and solidified by increasing the laser energy, so that the copper electrode and the transparent conductive film are connected with high quality, thereby improving the adhesion of the electrode to the surface of the transparent conductive film.

[0085] In one example, when the energy of the Nth laser scan is less than or equal to the energy of the first laser scan, the laser energy can be accumulated by increasing the value of N and performing multiple scans. The copper electrode can also be remelted and solidified to achieve high-quality connection between the copper electrode and the transparent conductive film, thereby improving the adhesion of the electrode to the surface of the transparent conductive film.

[0086] In one example, the laser energy of the Nth laser scan is higher than the laser energy of the first laser scan. Preferably, the Nth laser scan has a higher energy, and reducing the number of scans can also obtain a preset metal electrode, saving processing procedures.

[0087] In one example, the laser energy of the Nth laser scan is higher than the laser energy of the first laser scan.

[0088] In one example, in step (1), the thickness of the copper electrode slurry coating can be controlled by selecting coater parameters. Exemplarily, the thickness of the copper electrode slurry can be set to 1 μm-40 μm.

[0089] In one example, in step (1), the copper electrode slurry is disposed on the surface of the transparent conductive film by coating, and dried to obtain a dry copper electrode slurry coating. The drying method is not specifically limited, as long as the purpose of drying can be achieved. For example, a drying oven can be used for drying, the drying temperature can be 50°C-70°C, and the drying time can be 20-40 minutes.

[0090] In one embodiment, the method for preparing a solar cell grid electrode further comprises step (4): rinsing with deionized water to remove the remaining copper electrode slurry coating in the laser unprocessed area to obtain a heterojunction solar cell copper electrode. The cleaning solution is not limited to the deionized water listed above, and other cleaning solutions may also be applicable to the present invention.

[0091] The method for preparing a solar cell grid line electrode provided by the present invention can be interpreted as a method for preparing a heterojunction solar cell copper electrode by laser selective metal patterning.

[0092] In one example, the method for preparing a solar cell grid line electrode further includes a step of pre-cleaning a transparent conductive film, wherein the transparent conductive film is cleaned with a water-based cleaning agent before the copper electrode slurry is provided.

[0093] In one example, the water-based cleaning agent includes a nonionic surfactant, an anionic surfactant, a defoaming agent, and a phosphate detergent builder.

[0094] In one example, the nonionic surfactant as a main active agent may be selected from at least one of polyoxyethylene glycol lauryl alcohol ether (AEO-9), fatty alcohol polyoxyethylene ether (JFC-3) and alkylphenol polyoxyethylene ether (TX-10).

[0095] In one example, the compounded anionic surfactant is selected from at least one of sodium dodecyl diphenyl ether disulfonate (2A1), isooctyl alcohol polyoxyethylene ether phosphate and fatty acid hydroxyethane sulfonate.

[0096] In one example, the defoamer can be alcohols, amides, phosphates, polyethers, etc. For example, the defoamer is ethylenediamine PO-EO block copolymer (ED 3060), and other defoamers include tributyl phosphate, distearyl ethylenediamine, polyoxyethylene polyoxypropylene block copolymer, etc.

[0097] In one example, the phosphate detergent builder may be at least one of sodium tripolyphosphate, anhydrous sodium metaphosphate and sodium pyrophosphate.

[0098] In one example, based on the total weight of the water-based cleaning agent, the content of the nonionic surfactant is 16-21% by weight, the content of the anionic surfactant is 1-3% by weight, the content of the defoaming agent is 1-3% by weight, and the content of the phosphate detergent builder is 1.5-6% by weight. The remaining components are water, and the sum of the components is the total weight of the water-based cleaning agent, which is calculated as 100%.

[0099] In one example, based on the total weight of the water-based cleaning agent, the content of 2A1 is 1-3 weight %, the content of AEO-9 is 15-18 weight %, the content of JFC-3 is 1-3 weight %, the content of ED 3060 is 1-3 weight %, the content of sodium tripolyphosphate is 1-5 weight %, the content of anhydrous sodium metaphosphate is 0.5-1 weight %, and the remaining components are water.

[0100] In the present invention, the main components of the above-mentioned water-based cleaning agent are surfactants, detergent aids and buffer solutions, etc. The above-mentioned water-based cleaning agent is used to degrease and clean the silicon substrate of the heterojunction battery. During the cleaning process, the organic matter adsorbed on the surface of the silicon substrate can be removed by relying on the emulsification and saponification effects of the surfactant, thereby achieving the purpose of increasing the surface wettability and improving the surface tension, making the surface of the heterojunction battery easy to accept the coating, and improving the adhesion of the copper electrode slurry.

[0101] In one example, in step (2), the laser parameters used in the first laser scan include: laser pulse energy of 1nJ to 500nJ, laser scanning speed of 1mm / s to 500mm / s, defocus of +0mm to +2mm, laser pulse width of 100fs-20ps, frequency of 1KHz-70MHz, and laser wavelength of 300-1100nm.

[0102] In one example, in step (3), the laser parameters used in the Nth laser scan include: laser pulse energy of 25nJ to 2000nJ, laser scanning speed of 1mm / s to 500mm / s, defocus of +0mm to +2mm, laser pulse width of 100fs-20ps, frequency of 1KHz-70MHz, and laser wavelength of 300-1100nm.

[0103] In the present invention, copper circuits with different porosities, different aspect ratios and complex structures can be obtained by changing the laser parameters and the thickness of the copper electrode slurry coating, and copper circuits with different patterns can be obtained by arbitrarily changing the laser processing path, which has flexible controllability. The first laser scan and the Nth laser scan do not limit the laser pulse width and wavelength, and the pulse width can be femtosecond laser, picosecond laser or continuous laser; the wavelength can be 300nm-1100nm.

[0104] The method for preparing solar cell grid line electrodes provided by the present invention uses laser to selectively metal pattern the copper electrode slurry coating, which can directly obtain a copper line with a large aspect ratio and low resistivity, and will not cause damage to the laser unprocessed area, thereby improving the conversion efficiency of the solar cell. The method does not require multiple operations to increase the electrode thickness, nor does it require mask patterning and subsequent corrosion processes, and the process is simple. The method of multiple laser scanning can effectively increase the adhesion of the copper electrode, and can achieve the purpose of high efficiency and low cost.

[0105] In the method for preparing a solar cell grid line electrode provided by the present invention, there is no specific limitation on the laser processing system for the first laser scan and the Nth laser scan, and the laser processing system can be selected and assembled according to the specific type of the prepared metal electrode. The laser processing system used for the first laser scan and the Nth laser scan can be the same or different.

[0106] In one example, the first laser scan and the Nth laser scan use the same laser processing system.

[0107] In one example, the laser processing system includes a laser, an optical transmission system, a galvanometer system, and a three-dimensional moving platform. According to the needs of practical applications, the laser system may also include optical elements, a computer control system, a cooling system, and the like.

[0108] For example, Figure 4 As shown, the laser processing system includes a laser 9, an attenuation plate 10, an aperture 11, a glass slide 12, a beam expander 13, a reflector 14, a CCD image sensor 15, a scanning galvanometer 16, a field lens 17 and a three-dimensional moving platform 18. The laser can be a femtosecond laser, a picosecond laser or a continuous laser. After the laser outputs the laser, it passes through the attenuation plate, the aperture, the glass slide (which can be a 1 / 4 glass slide) and other optical elements, and then reaches the beam expander to expand the beam diameter, and then transmits to the galvanometer through the reflector, and the galvanometer focuses the beam onto the processing sample surface of the three-dimensional moving platform for subsequent laser selective processing.

[0109] In the laser processing system, the beam expander is used to expand the beam diameter and reduce the focused spot size, and the reflector is used to change the direction of light path transmission. When the laser processing system is working, the laser emits a Gaussian beam, which is redirected by the reflector and transmitted to the galvanometer, which focuses the beam onto the surface of the copper electrode slurry coating. The laser prepares the Cu grid line by inducing reduction of the copper electrode slurry coating according to the designed path.

[0110] In one embodiment, a method for preparing a solar cell grid electrode is described by referring to Figure 2 , Figure 3 and Figure 5 As shown, it includes the following steps:

[0111] (a) preparing a heterojunction battery substrate 8, which can be carried out in a conventional manner in the art;

[0112] (b) preparing a copper electrode slurry 6, and placing the slurry on the surface of the transparent conductive film 2 to form a coating;

[0113] (c) The first laser scanning selective metal patterning to prepare copper electrodes;

[0114] (d) The second laser scan is used to remelt and solidify the copper electrode;

[0115] (e) Removing the remaining copper electrode slurry coating in the laser 7 unprocessed area to obtain a heterojunction solar cell copper electrode.

[0116] The inventors of the present invention have found that since laser selective metal patterning is a photochemical reaction, the required temperature is relatively low, and it is difficult to achieve effective connection between the copper electrode and the transparent conductive film, and the adhesion is poor. Usually, sintering is required to improve the bonding strength between the copper electrode and the silicon substrate. However, the present invention uses a laser multiple scanning method to increase the laser energy to achieve remelting and solidification of the copper electrode, and achieve high-quality connection between the copper electrode and the transparent conductive film to achieve improved adhesion. At the same time, due to the high controllability of the laser, only the copper electrode can be processed, and no sintering is required, thereby avoiding damage to the amorphous silicon layer by the sintering furnace.

[0117] The fourth aspect of the present invention provides a photovoltaic cell, comprising a metal electrode, wherein the metal electrode is prepared using the copper electrode slurry described in the first aspect of the present invention, or the metal electrode is prepared using the method described in the third aspect of the present invention.

[0118] Exemplarily, the photovoltaic cell is a solar cell. The solar cell is a silicon solar cell, specifically a monocrystalline silicon solar cell, a polycrystalline silicon thin film solar cell, and an amorphous silicon thin film solar cell. Preferably, it is a heterojunction solar cell, and it can also be other types of solar cells. As long as the metal electrode of the solar cell is prepared by the copper electrode slurry provided by the present invention, or prepared by the method for preparing a metal electrode of the present invention, it is within the protection scope of the present invention.

[0119] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0120] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0121] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0122] Example A1

[0123] A copper electrode slurry, the formula of which is as follows:

[0124] Metal composition: nano copper oxide (CuO NP) with an average particle size of 30-50 nm, 10 parts by weight;

[0125] Dispersing reducing agent: polyvinyl pyrrolidone, 3.26 parts by weight;

[0126] Composite curing agent: bisphenol A epoxy resin (epoxy equivalent 182-192g / eq, viscosity 11000-14000cps), 0.5 parts by weight; PN-23J, 0.1 parts by weight;

[0127] Solvent: ethylene glycol, 6.76 parts by weight;

[0128] The copper electrode slurry is prepared by the following method:

[0129] (1) mixing the polyvinyl pyrrolidone and ethylene glycol in the formulated amounts in batches for multiple times (e.g., 4-5 times) and obtaining a mixed solution under the combined action of heating in a water bath at 45-65° C., magnetic stirring and ultrasonic vibration;

[0130] (2) Adding the formulated amount of nano copper oxide particles, epoxy resin and PN-23J to the mixed solution obtained in step (1) in batches for multiple times (for example, 4-5 times), and obtaining a copper electrode slurry under the combined action of heating in a water bath at 45-65° C., magnetic stirring and ultrasonic vibration.

[0131] Example A2

[0132] The method is carried out in accordance with Example 1, except that the copper electrode slurry has the following formula:

[0133] Metal composition: nano cuprous oxide (Cu2O NP), 10 parts by weight;

[0134] Dispersing reducing agent: polyvinyl pyrrolidone, 4 parts by weight;

[0135] Composite curing agent: polyurethane modified epoxy resin, 0.54 parts by weight; MY-25, 0.13 parts by weight;

[0136] Solvent: ethylene glycol, 10 parts by weight.

[0137] Example A3

[0138] The method is carried out in accordance with Example 1, except that the copper electrode slurry has the following formula:

[0139] Metal composition: CuO NP, 5 parts by weight, Cu2O NP, 5 parts by weight;

[0140] Dispersing reducing agent: polyvinyl pyrrolidone, 1.67 parts by weight;

[0141] Composite curing agent: acrylic modified epoxy resin, 0.43 parts by weight; PN-23J, 0.07 parts by weight;

[0142] Solvent: ethylene glycol, 6.25 parts by weight.

[0143] Example A4 Group

[0144] This group of examples is used to illustrate the effect of adjusting the components and proportions in the composite curing agent on the performance of the copper electrode slurry.

[0145] Example A4-1 is carried out in accordance with Example 1, except that the composite curing agent is: epoxy resin, 0.83 parts by weight; PN-23J, 0.17 parts by weight;

[0146] Example A4-2 is carried out with reference to Example 1, except that the composite curing agent is: epoxy resin, 0.3 parts by weight; PN-23J, 0.3 parts by weight;

[0147] Example A4-3 is carried out with reference to Example 1, except that the composite curing agent is: epoxy resin, 0.5 parts by weight; PN-23J, 0.05 parts by weight; MY-25, 0.05 parts by weight.

[0148] Example A5

[0149] This group of examples is used to illustrate the effect of adjusting the proportions of different components on the performance of copper electrode slurry.

[0150] Example A5-1 was carried out in accordance with Example 1, except that CuO NP, 10 parts by weight; polyvinyl pyrrolidone, 5 parts by weight;

[0151] Example A5-2 was carried out in accordance with Example 1, except that CuO NP, 10 parts by weight; solvent, 20 parts by weight;

[0152] Example A5-3 is carried out with reference to Example 1, except that polyvinyl pyrrolidone is used in an amount of 0.67 parts by weight and solvent is used in an amount of 6.76 parts by weight.

[0153] Comparative Example A1

[0154] The same process is carried out as in Example 1, except that 0.6 parts by weight of epoxy resin is used as a curing agent.

[0155] Comparative Example A2

[0156] The same process is carried out as in Example 1, except that 0.6 parts by weight of PN-23J is used as a curing agent.

[0157] Comparative Example A3

[0158] The same method is carried out as in Example 1, except that the composite curing agent is 0.2 parts by weight of epoxy resin and 0.05 parts by weight of PN-23J.

[0159] Example B1

[0160] A method for preparing a solar cell copper grid electrode comprises the following steps:

[0161] (1) preparing a heterojunction battery substrate and depositing a transparent conductive film (ITO) on both sides of the substrate;

[0162] Specifically, the preparation of the heterojunction battery substrate includes the following steps: after texturing and cleaning the n-type monocrystalline silicon wafer, an intrinsic amorphous silicon film (ia-Si:H) and a p-type amorphous silicon film (pa-Si:H) are sequentially deposited on the front of the n-type monocrystalline silicon wafer (c-Si), and then an intrinsic amorphous silicon film (ia-Si:H) and an n-type amorphous silicon film (na-Si:H) are sequentially deposited on the back of the silicon wafer to form a back surface field; a transparent oxide conductive film is deposited on both sides of the battery. The texturing and cleaning, the deposition method of the intrinsic amorphous silicon film, and the deposition method of the transparent conductive film are as described above and will not be repeated here. The specific process parameters are carried out in accordance with the conventional operating methods in the field.

[0163] The thickness of the intrinsic amorphous silicon film (ia-Si:H) is 5 nm;

[0164] The thickness of the p-type amorphous silicon film (pa-Si:H) is 5 nm;

[0165] The thickness of the n-type amorphous silicon film (na-Si:H) is 5 nm;

[0166] The thickness of the transparent conductive film (ITO) is 100 nm.

[0167] (2) Using a water-based cleaning agent to clean the surface of the ITO of the heterojunction battery to remove impurities and grease on the surface of the ITO; wherein the total weight of the water-based cleaning agent is used as a reference, the content of 2A1 is 2 weight%, AEO-9 is 16 weight%, JFC-3 is 2 weight%, ED 3060 is 2 weight%, sodium tripolyphosphate is 4 weight%, anhydrous sodium metaphosphate is 0.8 weight%, and the remaining components are water.

[0168] (3) Using a four-sided coater, the copper electrode slurry prepared in Example A1 is applied to the surface of the heterojunction battery ITO cleaned in step (2), and dried in a drying oven at 50° C.-70° C. for 20-40 min to obtain a dry copper electrode slurry coating with a coating thickness of 7 μm-15 μm.

[0169] (4) The first laser scan is used to selectively metal pattern the dried copper electrode slurry coating according to the designed path; the processing parameters of the first laser scan are: laser pulse energy of 79nJ, laser scanning speed of 6mm / s, defocus of +0.6mm, number of laser scans of 1, laser pulse width of 9ps, repetition frequency of 2MHz, and laser wavelength of 532nm.

[0170] (5) The reduced copper electrode obtained in step (4) is subjected to a second laser scanning, and the processing parameters of the second laser scanning are: laser pulse energy of 500 nJ, laser scanning speed of 6 mm / s, defocusing amount of +0.6 mm, number of laser scanning times of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm.

[0171] (6) Rinse with deionized water to remove the remaining copper electrode slurry coating in the unprocessed area to obtain a heterojunction solar cell copper electrode.

[0172] The first laser scan and the second laser scan use the same laser processing system, refer to Figure 2 The schematic diagram of the laser processing system includes a picosecond laser, an attenuation plate, an aperture, a quarter glass, a 4x beam expander, a reflector, a CCD image sensor, a scanning galvanometer, a field mirror, and a three-dimensional moving platform. When the laser processing system is working, the picosecond laser emits a Gaussian beam, which is redirected by the reflector and transmitted to the galvanometer, which focuses the beam onto the surface of the copper electrode slurry coating. The laser prepares the Cu gate line by inducing reduction of the copper electrode slurry coating according to the designed path.

[0173] The three-dimensional morphology of the Cu gate line obtained in this embodiment is shown in the schematic diagram of the structure. Figure 6 As shown, a copper electrode with a uniform and fine surface and a line width of about 40 μm can be directly prepared by laser selective metal patterning. It should be noted that the copper electrode line width prepared by this laser processing system can be as small as 16 μm, but the improvement of resolution will lead to a decrease in resistivity, and the minimum width of the prepared copper electrode is related to the laser spot diameter. Changing the laser equipment can obtain a lower line width.

[0174] The copper circuit structure obtained in this embodiment is dense and can obtain a lower porosity. According to the element composition analysis by X-ray energy spectrum, the Cu:O ratio of the copper electrode obtained in this embodiment is increased from 1.8:1 before processing (copper electrode slurry) to 23.2:1, and the Cu / O content is greatly improved, reflecting that the Cu element is fully reduced at this time.

[0175] Examples B2-B9

[0176] Examples B2-B9 are carried out with reference to Example 1, except that in step (3) of Example B2 and Example B3, the copper electrode slurries prepared in Examples A2 and A3 are used respectively; in step (3) of Example B4-B6, the copper electrode slurries prepared in Examples A4-1, A4-2 and A4-3 are used respectively; in step (3) of Example B7-B9, the copper electrode slurries prepared in Examples A5-1, A5-2 and A5-3 are used respectively.

[0177] Example B10

[0178] The process was carried out with reference to Example B1, except that the processing parameters of the first laser scan were: laser pulse energy of 100 nJ, laser scanning speed of 5 mm / s, defocus of +0.6 mm, laser scanning number of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. Compared with Example B1, Example B10 also obtained a copper electrode with good surface morphology, low porosity, and dense structure.

[0179] Example B11

[0180] The process was carried out with reference to Example B1, except that the processing parameters of the first laser scan were: laser pulse energy of 100 nJ, laser scanning speed of 8 mm / s, defocus of +0.6 mm, laser scanning number of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. The prepared Cu circuit was compared with Example B1. Due to the increase in laser scanning speed and the reduction reaction time, the copper electrode obtained in this example had poor continuity, but the overall morphology was complete.

[0181] Example B12

[0182] The process was carried out with reference to Example B1, except that the processing parameters of the first laser scan were: laser pulse energy of 79nJ, laser scanning speed of 6mm / s, defocus of +0.8mm, laser scanning number of 1, laser pulse width of 9ps, repetition frequency of 2MHz, and laser wavelength of 532nm. The prepared Cu circuit was compared with Example B1. Due to the increase in defocus and the decrease in laser energy density, the Cu circuit morphology obtained in this example had a small number of defects, but the overall morphology was complete.

[0183] Example B13

[0184] The process was carried out with reference to Example B1, except that the processing parameters of the second laser scanning were: laser pulse energy of 500nJ, laser scanning speed of 4mm / s, defocus of +0.8mm, laser scanning number of 1, laser pulse width of 9ps, repetition frequency of 2MHz, and laser wavelength of 532nm. The prepared Cu circuit was compared with Example B1, and the present embodiment can obtain a copper electrode with good surface morphology, low porosity, and dense structure.

[0185] Example B14

[0186] The process was carried out with reference to Example B1, except that the processing parameters of the second laser scan were: laser pulse energy of 600 nJ, laser scanning speed of 6 mm / s, defocus of +1.0 mm, laser scanning number of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. The prepared Cu circuit was compared with Example B1, and the present embodiment can obtain a copper electrode with good surface morphology, low porosity, and dense structure.

[0187] Example B15

[0188] The process is carried out in accordance with Example 1, except that after the laser scanning in step (5) is completed, 50 laser scans are further performed, and the processing parameters of the 50 laser scans are: laser pulse energy of 35 nJ, laser scanning speed of 6 mm / s, defocus of +0.6 mm, number of laser scans of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm.

[0189] Comparative Examples B1-B3

[0190] Comparative Examples B1-B3 were carried out with reference to Example B1, except that in step (3) of Comparative Examples B1-B3, the copper electrode slurries prepared in Comparative Examples A1, A2 and A3 were used respectively.

[0191] Comparative Example B4

[0192] The same method was used as in Example B1, except that the laser parameters used in the first laser scan were: laser pulse energy of 35 nJ, laser scanning speed of 6 mm / s, defocus of +0.6 mm, laser scanning number of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. The lower energy was insufficient to completely reduce CuO to Cu, and the resulting copper circuit had a poor morphology.

[0193] Comparative Example B5

[0194] The method was carried out with reference to Example B1, except that the laser parameters used in the first laser scan were: laser pulse energy of 100 nJ, laser scanning speed of 2 mm / s, defocus of +0.6 mm, laser scanning number of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. The prepared Cu circuit was compared with Example B1. The copper circuit obtained in this comparative example was severely oxidized due to the slow laser scanning speed.

[0195] Comparative Example B6

[0196] The method was carried out with reference to Example B1, except that the laser parameters used in the first laser scan were: laser pulse energy of 79nJ, laser scanning speed of 6mm / s, defocus of +0.2mm, laser scanning number of 1, laser pulse width of 9ps, repetition frequency of 2MHz, and laser wavelength of 532nm. The prepared Cu circuit was compared with Example B1. Due to the small spot diameter (due to the small defocus), the laser energy density was too large, the copper electrode slurry coating was ablated, and a good copper circuit could not be restored.

[0197] Comparative Example B7

[0198] The process was carried out with reference to Example B1, except that the processing parameters of the second laser scan were: laser pulse energy of 800 nJ, laser scanning speed of 6 mm / s, defocus of +0.6 mm, number of laser scans of 1, laser pulse width of 9 ps, repetition frequency of 2 MHz, and laser wavelength of 532 nm. The metallographic image of the prepared Cu circuit was tested in the same manner as in Example B1, and it was found that due to the excessive energy of the second laser scan, the copper electrode was ablated and gasified, and a good copper circuit could not be obtained.

[0199] Comparative Example B8

[0200] The same procedure is carried out as in Example B1, except that the second laser scan is not performed.

[0201] Comparative Example B9

[0202] The same method is carried out as in Example B1, except that in step (2), ethanol is used instead of the water-based cleaning agent.

[0203] Test Case

[0204] (1) The resistivity of the metal electrodes of the above-mentioned Examples B1-B15, Comparative Examples B1-B3, and Comparative Examples B8-B10 was obtained by testing using a four-probe method. The results are recorded in Table 1.

[0205] (2) The above-mentioned embodiments B1-B15, comparative examples B1-B3, and comparative examples B8-B10 were tested to obtain the binding force of the metal electrodes, and the hundred-grid method was used for testing. The test results were divided into six levels: 0B, 1B, 2B, 3B, 4B, and 5B. 0B-5B means that the binding force becomes larger, that is, the binding force of 5B is the strongest. The results are recorded in Table 1.

[0206] Table 1

[0207]

[0208]

[0209] It can be seen from the experimental data in Table 1 that the method of preparing heterojunction solar cell copper electrodes by laser selective metal patterning, combined with the copper electrode slurry provided by the present invention, can obtain grid line electrodes with high porosity and bonding strength, and the laser multiple scanning method can effectively increase the bonding strength of the copper electrode.

[0210] In addition, it can be seen from the above experimental data that changing the total content of the composite curing agent will change the resistivity and adhesion. A high content of the composite curing agent will lead to an increase in the resistivity (see Example B4), and a low content of the composite curing agent will affect the adhesion (see Comparative Example B3). The internal ratio of the composite curing agent affects the curing effect, i.e., the bonding force, and has little effect on the resistivity (see Examples B5 and B6). Combined with multiple laser processing, the resistivity can be reduced and the adhesion can be improved.

[0211] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A copper electrode slurry, characterized in that: It comprises a metal composition, a dispersing reducing agent, a composite curing agent and optionally a solvent; the metal composition comprises at least copper powder, and optionally gold powder and / or silver powder; the composite curing agent comprises a thermosetting resin and a latent curing agent; Wherein, the mass ratio of the metal composition to the composite curing agent is (7-30):

1.

2. The copper electrode slurry according to claim 1, wherein The thermosetting resin is selected from at least one of epoxy resin, polyurethane-modified epoxy resin, acrylic-modified epoxy resin, polyamide resin, polyurethane resin and acrylic resin; And / or, the latent curing agent includes a latent amine curing agent and / or an imidazole curing agent; And / or, the mass ratio of the thermosetting resin to the latent curing agent is (4-6):1; And / or, the mass ratio of the metal composition to the composite curing agent is (15-20):

1.

3. The copper electrode slurry according to claim 1, wherein The reducing dispersant is selected from at least one of polyvinyl pyrrolidone and its derivatives; And / or, the mass ratio of the metal composition to the dispersing reducing agent is (2-9):1, preferably (2.5-6):

1.

4. The copper electrode slurry according to any one of claims 1 to 3, wherein: The metal composition includes nano copper oxide and / or nano cuprous oxide; And / or, the solvent is selected from C1-C6 low-carbon alcohols; And / or, the mass ratio of the metal composition to the solvent is (0.3-2):1, preferably (1-1.6):1; And / or, the mass ratio of the solvent to the dispersing reducing agent is (1.8-14):1, preferably (2-5):

1.

5. A metal electrode, characterized in that: The method is prepared by using the copper electrode slurry described in any one of claims 1 to 4.

6. The metal electrode according to claim 5, wherein: The metal electrode is a metal electrode in a solar cell, a secondary battery, a circuit board, a light-emitting diode or a microelectronic device; Preferably, the metal electrode is a grid line electrode of a solar cell.

7. A method for preparing a metal electrode, characterized in that: The metal electrode is prepared by using the copper electrode slurry described in any one of claims 1 to 4 and a laser process.

8. The method according to claim 7, wherein: The method for preparing a solar cell grid line electrode comprises the following steps: (1) placing the copper electrode slurry on the surface of the transparent conductive film of the silicon substrate; (2) performing a first laser processing on the copper electrode slurry coating on the surface of the transparent conductive film in step (1); (3) performing laser processing N times on the copper electrode slurry of step (2), where N≧2; The laser energy of the Nth laser processing is higher than the laser energy of the first laser processing.

9. The method according to claim 8, wherein: The step of pre-cleaning the transparent conductive film is also included, wherein the transparent conductive film is cleaned with a water-based cleaning agent before the copper electrode slurry is set; Preferably, based on the total weight of the water-based cleaning agent, the content of the sulfonyl aryl sulfonate surfactant is 1-3 weight %, the content of the polyoxyethylene fatty alcohol ether surfactant is 16-21 weight %, the content of the polyether defoamer is 1-3 weight % and the content of the phosphate detergent aid is 1.5-6 weight %.

10. A photovoltaic cell comprising a metal electrode, characterized in that: The metal electrode is prepared by using the copper electrode slurry described in any one of claims 1-4, or the metal electrode is prepared by using the method described in any one of claims 7-9.

Citation Information

Patent Citations

  • Conductive copper paste for laser and preparation method of conductive copper paste

    CN105336387A

  • Electrode slurry for heterojunction solar cell and preparation method thereof

    CN111048233A

  • Copper coating method used for aluminum nitride ceramic and combining screen printing and laser surface deposition

    CN111943708A

  • Method for preparing flexible copper circuit by laser-induced reduction sintering of copper oxide ink

    CN111970842A

  • Solar cell production method and solar cell

    CN115132859A

Cited By

  • Manufacturing method of solar cell and solar cell

    CN119744023A

  • Method for manufacturing a solar cell and solar cell

    CN119744023B

  • Manufacturing method of solar cell and solar cell

    CN120603357A